مدى وعي المجتمع حول سلامة المواد الغذائية المعلبة - سلوى عبدالنبي سالم; نادية اللافي الأسطى (Surman Journal of Science and Technology, 2026)
This study aimed to examine the extent of citizens’ awareness of the safety of the food they consume and the level of their concern for their health through selecting foods of appropriate quality and nutritional value in terms of ingredients. It also sought to explore the reality of public knowledge regarding the concept of food safety, including awareness of food components, production processes, and storage methods. Using a descriptive approach, data were collected from journals and books, and a questionnaire was administered to identify the opinions of the study sample, which consisted of 60 individuals from the Abu Salim area. Statistical methods such as the arithmetic mean and standard deviation were employed. The most important findings indicated a strong preference for consuming fresh natural foods rather than ready-made meals, a high level of concern regarding the safety of foods purchased from stores, and weak knowledge about the sources of unsafe foods. In addition, there was limited attention to reading production and expiration dates or food labels. The study recommended intensifying awareness campaigns on safe food storage practices and proper handling methods to prevent contamination (as the statements related to these aspects recorded the lowest means in the third axis). It also emphasized directing awareness efforts toward identifying sources of unsafe foods (as this statement recorded the lowest mean in the first axis), in order to help citizens make more informed purchasing decisions.